Manufacturing of composite (Ni-Al +Al2O3-ZrO2) by using Flame Thermal Spray Technique. - I.K Jassim; S.Y. Darweesh; S.M. Nuri (Tikrit Journal of Pure Science)
Flame Thermal Spray technique was used to produce matrix composite of ZrO2 (25%) reinforced with Alumina (25%) with (Al-Ni) (50)% have been spray into base substrate of stainless steel type (316L). All samples were grit blasted as initial preparation state and all spraying done at different distances from substrate (12, 14, 16,17, 18, 20) cmtest of stiffness, porosity and adhesion has been experienced on the compound layer which produced to study the effect of changing the spraying distance on the layer characteristic. All samples were heated at (950, 1050) ºC for(1/2hr). The results before and after heat treatment show that the optimum condition for spraying distance at (16 cm) and heat treatment at (1050 ºC) which are most effective to give best results  especially hardness, porosity and adherence bond.